Pengaruh Citra Merek Dan Harga Terhadap Keputusan Pembelian Pada A&W Fast Food Restaurant Karawang: manajemen pemasaran (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
This study aims to examine and analyze the influence of brand image and price on purchasing decisions for fast food restaurants A&W KarawanG. The research was conducted using descriptive and verification methods, namely: collecting, presenting, analyzing and testing hypotheses and making conclusions and suggestions. Samples were collected using the Slovin formula and probability sampling technique using simple random sampling which then resulted in 347 samples from 2,612 populations. The analytical technique used is the technique of scale range analysis and path analysis with the help of the Method of Successive Interval (MSI), Microsoft Excel 2010 computer program and SPSS version 25 application. 1,266 with agreed criteria. The price shows an average value of 1,258 with agreed criteria. Purchasing Decision shows an average value of 1,241 with the criteria for agreeing. The correlation coefficient between the Brand Image and Price variables obtained a value of 0.530 which means it has a moderate, positive and significant correlation level between Brand Image and Price. The partial effect of Price on Purchase Decisions is 0.133, which is greater than Brand Image, which has a value of 0.059. So it can be stated that the price contributes more to the Purchase Decision compared to the Brand Image. The simultaneous influence of Brand Image and Price on Purchasing Decisions is 19.2% while the remaining 80.8% is another variable not examined.